Students' approaches to learning: a reviewed literature / Nur Fakhzan Marwan - Marwan, Nur Fakhzan (2004)
The way students approach their learning is related to the quality of their learning outcomes. Thus, efforts should also be directed towards understanding how students learn. There are two general learning approaches: surface and deep approaches. These concepts were first appeared in the literature from three independent sources in the mid-1970s. In the United Kingdom, Noel Entwistle leads a group which explore student learning through interview and questionnaire across a wide range of disciplines. In Sweden, at Gothenburg University, Roger Saljo and others develop new ways of studying how students approach reading tasks. In Australia, John Biggs of the Newcastle University examines the motives and strategies of university students and develops the 3P model, which describes three processes that students use in studying. These researches on how students learn in higher education, how they develop and change, and what influence their approaches to learning, has provided a coherent, rich and illuminating picture for better understanding in designing educational programs, which will provide students with the opportunity to develop required skills and to improve their educational experience.